Peranan Pendidikan Kewarganegaraan sebagai pilar pendidikan hak asasi manusia - Warsono Warsono (Jurnal Civics: Media Kajian Kewarganegaraan, 2006)
Human Rights are a fundamental problem in every country. especially in the developing countries such as Indonesia. Even though, the state had given protection of human right for everybody, but in Indonesia there are many breakdowns of it. As a democratic state, Indonesia has to regard human right. It is because the human rights were the core of democratic principle. So, the human rights must be trained in the school for every student. By using this way, everybody can know what their rights and obligations very well Civics education can be a vehicle for this goal, because it's one of lessons that talk about human rights and be learned in all school.